Maternal Vitamin B12 Status During Pregnancy and Its Association With Outcomes of Pregnancy and Health of the Offspring: A Systematic Review and Implications for Policy in India - Behere, Rishikesh V.; Deshmukh, Anagha S.; Otiv, Suhas; Gupte, Mohan D.; Yajnik, Chittaranjan S. (Frontiers in Endocrinology, 2021)
Background: Vitamins B12 and folate participate in the one-carbon metabolism cycle and hence regulate fetal growth. Though vitamin B12 deficiency is widely prevalent, the current public health policy in India is to supplement only iron and folic acid for the prevention of anaemia. Prompted by our research findings of the importance of maternal vitamin B12 status for maternal and child health, we evaluated available literature evidence using a systematic review approach, to inform policy. Methods: A systematic search was performed for relevant Indian studies reporting maternal vitamin B12 status (dietary intake or blood concentrations), and/or metabolic markers of vitamin B12 deficiency (homocysteine, methylmalonic acid) or haematological indices during pregnancy and their associations with outcomes of pregnancy, infancy or in later life. Intervention trials of vitamin B12 during pregnancy were also included. Quality of evidence was assessed on the Grading of Recommendations Assessment, Development, and Evaluation(GRADE) system. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA) statement. Results: Of the 635 articles identified, 46 studies met the inclusion criteria (cohort studies-26, case-control studies-13, RCT’s -7). There is a high prevalence of vitamin B12 deficiency in Indian women during pregnancy (40-70%) (3 studies). Observational studies support associations (adjusted for confounders) of lower maternal B12, higher homocysteine or an imbalance between vitamin B12-folate status with a higher risk of NTDs (6 studies), pregnancy complications (9 studies), lower birth weight (10 studies) and adverse longer-term health outcomes in the offspring (cognitive functions, adiposity, insulin resistance) (11 studies). Vitamin B12 supplementation (7 RCT’s) in pregnancy showed a beneficial effect on offspring neurocognitive development and an effect on birth weight was inconclusive. There is high-quality evidence to support the role of low maternal vitamin B12 in higher risk for NTD and low birth weight and moderate-quality evidence for higher risk of gestational diabetes and later life adverse health outcomes in offspring. Conclusion: There is a high prevalance of B12 deficiency in Indian women during pregnancy and the level of evidence supports adding vitamin B12 to existing nutritional programs in India for extended benefits on outcomes in pregnancy and offspring health besides control of anaemia.